Therapeutic approaches to cerebral vasospasm complicating ruptured aneurysm - Mohamed Barbarawi; Sarah F. Smith; Mohamed Abu Jamous; Hazem Haboub; Qudsieh Suhair; Shboul Abdullah (MDPI AG, 2009)
Cerebral vasospasm is a serious complication of ruptured aneurysm. In order to avoid short- and long-term effects of cerebral vasospasm, and as there is no single or optimal treatment modality employed, we have instituted a protocol for the prevention and treatment of vasospasm in patients suffering aneurysmal sub-arachnoid hemorrhage (SAH). We then reviewed the effectiveness of this protocol in reducing the mortality and morbidity rate in our institution. In this study we present a retrospective analysis of 52 cases. Between March 2004 and December 2008 52 patients were admitted to our service with aneurysmal SAH. All patients commenced nimodipine, magnesium sulphate (MgSO4) and triple H therapy. Patients with significant reduction in conscious level were intubated, ventilated and sedated. Intracranial pressure (ICP) monitoring was used for intubated patients. Sodium thiopental coma was induced for patients with refractory high ICP; angiography was performed for diagnosis and treatment. Balloon angioplasty was performed if considered necessary. Using this protocol, only 13 patients (25%) developed clinical vaso-spasm. Ten of them were given barbiturates to induce coma. Three patients underwent transluminal balloon angioplasty. Four out of 52 patients (7.7%) died from severe vasospasm, 3 patients (5.8%) became severely disabled, and 39 patients (75%) were discharged in a condition considered as either normal or near to their pre-hemorrhage status. Our results confirm that the aforementioned protocol for treatment of cerebral vasospasm is effective and can be used safely.